Innovate for agriculture: Young ICT entrepreneurs overcoming challenges and transforming agriculture - Rahman, Reem; Fong, Jocelyn (Technical Centre for Agricultural and Rural Cooperation, 2016)
The report introduces 30 young innovators, 21 featured with full stories, and nine other "innovators to watch". They come from countries including Barbados, Botswana, Cameroon, Côte d'Ivoire, Kenya, Nigeria, Uganda, Jamaica, Senegal, Tanzania. The publication presents a multidimensional picture of the emerging field of ICT entrepreneurship in agriculture in developing countries. It describes challenges but also successes already achieved. It contains advice for aspiring agtech entrepreneurs as well as recommendations from youth on how to support their ventures.